An old species and a new frontier: Some thoughts on the taxonomy of Homo erectus - Wang, Qian; Tobias, Philip V. (Polskie Towarzystwo Antropologiczne, 2001)
The taxonomic impact on Homo erectus induced by a "preerctus-out-of-Africa" paradigm is preliminarily discussed in this article. Some of the early Homo species in Asia should be allocated to another taxon rather than to H. erectus, although teir real identities are not yet readily apparent. Asian H. erectus may be taxonomically distinct from African H. ergaster. Differences between two samples of H. erectus from Java and China, suggesting taxonomic diversity or only geographical variances between these subset, need further study. Reasons are advanced against the proposal to lump H. erecus into H. sapiens.
Keywords: Genus Homo; Java; China; Out-of-Africa